Effect of Turmeric Powder Supplementation to The Age of Sexual Maturity, Physical, and Chemical Quality of The First Japanese Quail’s (Coturnix japonica) Egg - Tyas Rini Saraswati; Silvana Tana (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2016)
The experiment was conducted to determine the effect of turmeric powder supplementation to the age of sexual maturity, physical, and chemical quality of the first Japanese quail’s (Coturnix japonica) egg. Forty five quails were assigned into a completely randomized design with three treatments (levels of turmeric powder, i.e., 0; 54; and 108 mg/quail/day) and each treatment used 15 quails. Turmeric powder supplementation was conducted before sexual maturity. Feed and drinking water provided ad libitum. Observed egg is an egg that was first produced. Parameters measured were the age of sexual maturity, feed intake, body weight, physical qualities which include: weight of egg, long axis, short axis, weight and thickness of shell, yolk index, Haugh unit, egg shell index. Whereas the observed chemical quality were cholesterol, HDL, LDL, protein, vitamin B12, vitamin A in eggs and egg shell calcium levels. The results showed that administration of turmeric powder can accelerate the age of maturity, increasing the levels of protein, HDL, vitamin A and B12 in eggs, decreasing the cholesterol and LDL content in eggs, but did not affect feed intake, physical quality of eggs and egg shell calcium levels. Based on the results of this study, it can be concluded that supplementation of turmeric powder improve the chemical quality of Japanese quail eggs (Coturnix japonica), so it is good for the development of quail embryos as well as for consumption.How to CiteSaraswati, T. R., Tana, S. (2016). Effect of Turmeric Powder Supplementation To The Age of Sexual Maturity, Physical, and Chemical Quality of The First Japanese Quail’s (Coturnix japonica) Egg. Biosaintifika: Journal of Biology Biology Education, 8(1), 18-24.